Identification of α-Glucosidase Inhibitors and Assessment of Human Safety from 491 Native Plant Species of Jeju Island - Ho-Min Kang; Jin-Kyu Kang; Pomjoo Lee; Chang-Gu Hyun (Cosmetics)
In contemporary society, obesity has become a critical public health issue driven by lifestyle modifications such as unhealthy dietary patterns, physical inactivity, and aging. Beyond its aesthetic implications, obesity is a significant etiological factor for metabolic disorders, including type 2 diabetes and cardiovascular diseases. With increasing emphasis on weight management and holistic health, the demand for slimming cosmetics has risen substantially. In particular, the formulation of natural-origin slimming cosmetic ingredients that facilitate lipolysis and improve dermal elasticity is being actively investigated, presenting a compelling balance of safety and efficacy. This study examined the bioactivities of 570 plant extracts sourced from Jeju Island to evaluate their potential as cosmetic raw materials. The α-glucosidase inhibitory activity was analyzed to determine their antidiabetic potential. Among the tested extracts, 18 species, including Rumex japonicus (IC50, 0.93 ± 0.21 μg/mL), Rhynchosia volubilis (IC50, 1.2 ± 0.16 μg/mL), and Arachniodes standishii (IC50, 4.88 ± 0.89 μg/mL), exhibited substantially lower IC50 values compared to the positive control, acarbose (IC50, 251.17 ± 22.67 μg/mL). These findings highlight the potential of these extracts as innovative α-glucosidase inhibitors, potentially serving as alternatives to conventional pharmacological agents. Additionally, the safety of the 18 extracts for topical application was assessed via cytotoxicity assays using human keratinocyte (HaCaT) cells and primary skin irritation tests. The results indicated no cytotoxicity in HaCaT cells and no evidence of dermal irritation at concentrations deemed non-toxic to the cells. In summary, these 18 plant extracts from Jeju Island exhibit significant promise as multifunctional cosmetic ingredients, combining slimming properties through adipogenesis inhibition with skin-enhancing benefits.